2019
DOI: 10.1103/physrevmaterials.3.104601
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the donor impurity band in mixed valence insulators

Abstract: In traditional semiconductors with large effective Bohr radius, an electron donor creates a hydrogen-like bound state just below the conduction band edge. The properties of the impurity band arising from such hydrogenic impurities have been studied extensively during the last 70 years. In this paper we consider whether a similar bound state and a similar impurity band can exist in mixed-valence insulators, where the gap arises at low temperature due to strong electron-electron interactions. We find that the st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 61 publications
(126 reference statements)
3
30
0
Order By: Relevance
“…The compound SmB 6 has been of great ongoing research interest as a Kondo insulator [1,2], a mixed-valent system [3][4][5], and as the prototypical example of a strongly correlated topological insulator [6][7][8][9][10]. A topologically nontrivial interpretation of the band structure is supported by angle resolved photoemission spectroscopy (ARPES) investigations [10][11][12][13][14][15], and is consistent with measurements of surface state spin texture [16].…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…The compound SmB 6 has been of great ongoing research interest as a Kondo insulator [1,2], a mixed-valent system [3][4][5], and as the prototypical example of a strongly correlated topological insulator [6][7][8][9][10]. A topologically nontrivial interpretation of the band structure is supported by angle resolved photoemission spectroscopy (ARPES) investigations [10][11][12][13][14][15], and is consistent with measurements of surface state spin texture [16].…”
Section: Introductionmentioning
confidence: 65%
“…4(c)]. A likely explanation is that rather than generating incoherent scattering, impurity doping results in strong coherent local screening as suggested in recent theoretical work [5,31], and should therefore be thought of as contributing to real self-energy rather than imaginary [32]. As such, the self-energy components would not be linearly additive.…”
Section: B Topological Band Coherencementioning
confidence: 98%
“…These local moments in the lattice would be screened, and the amount of screening, and thus the magnetization, would oscillate in magnetic field [46]. Still another report focused on nonmagnetic impurities, which were found to form a deep impurity band as in a metal as well as an in-gap band [47], and another proposal revisited the idea of in-gap impurity states [48]. Historically, hydrogenic in-gap impurity states like those found in doped semiconductors were proposed in SmB 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Instead, Ref. [48] showed that the hybrid band structure of SmB 6 has its own model of hydrogenlike in-gap impurity states. Interestingly, the density of defects required for an insulator-to-metal transition is orders of magnitude higher than the required density for an insulator-metal transition in parabolic semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…Our surprising finding of quantum oscillations in the magnetic torque of floating zone-grown single crystals of SmB 6 ( Tan et al., 2015 ), despite the bulk insulating gap, has given rise to multiple proposals for their potential origin. Physical mechanisms proposed as potential explanations for the observed quantum oscillations include bulk in-gap low energy excitations ( Tan et al., 2015 ; Hartstein et al., 2018 ), two-dimensional surface conduction states ( Li et al., 2014 ), tunneling across the bulk insulating gap ( Knolle and Cooper, 2015 , 2017 ), and impurity inclusions ( Thomas et al., 2019 ; Fuhrman et al., 2018 ; Fuhrman and Nikolić, 2020 ), among others ( Baskaran, 2015 ; Knolle and Cooper, 2015 , 2017 ; Erten et al., 2016 , 2017 ; Chowdhury et al., 2018 ; Sodemann et al., 2018 ; Thomson and Sachdev, 2016 ; Skinner, 2019 ; Peters et al., 2019 ; Liu and Balents, 2017 ; Shen and Fu, 2018 ; Valentine et al., 2016 ; Harrison, 2018 ; Zhang et al., 2016 ; Pal, 2017 ; Riseborough and Fisk, 2017 ; Grubinskas and Fritz, 2018 ; Sakhya and Maiti, 2020 ; Pixley et al., 2018 ; Ram and Kumar, 2017 ; Anderson, 1992 ; Coleman et al., 1993 ; Motrunich, 2006 ; Grover et al., 2010 ; Paul et al., 2007 ; Kishigi and Hasegawa, 2014 ).…”
Section: Introductionmentioning
confidence: 99%